Knowledge, Attitude and Practice among Myope Students - Naseer Fatima, Muhammad Siddique, Omair Azeem, Maryam Jabbar, Faisal Rashid, Muhammad Hamza Shahid (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The purpose of this study was to evaluate the knowledge, attitude, and practice of myope students at The University of Faisalabad. Methods: Descriptive study was conducted to interpret the medical students’ knowledge, attitudes, and practice about myopia. An organized questionnaire with 14 questions was created. The research was carried out between December 2021 and April 2022 in different medical colleges of Punjab. The sample size was 300 female adolescents ranging in age from 18 to 26 years. Results: 300 Asian myopic medical students participated in this study. All were females. The subjects were divided into three groups on the basis of classification of myopia. 1. High myopes 2.Moderate Myopes 3.Low myopes. 234 students had heard of myopia, while 42 students (14%) had not. Out of the 300 participants, 227 (75.6%) were aware that they have myopia, and 230 (76.6%) students are aware that myopes were unable to see clearly at a distance. 245 participants (81.6%) had a history of myopia in their families. Only 81 (or 27% of the total) for a routine yearly eye exam visited an eye doctor or optometrist. 121 (40.3%) of them preferred contact lenses to glasses. Only 57 individuals (19%) wear glasses constantly while 193 people (64.3%) didn’t. 134 respondents (44.6%) had a bad attitude regarding those who wear glasses. On average, 210 students (70%) spent fewer than 6 hours outside whereas 189 students (63 %) spent more than 6 hours on screens. Conclusion: In this study parental history was positive and screen time was more than 6 hours. Outdoor activities were reduced and also vitamin A intake was reduced. All above possibility were leading factors to progression of myopia in medical students.